Development of a Validation System (SVeR) Based on the Open Journal System for Testing the Validity of Learning Tools - Safrizal SAFRIZAL; Syamsul Bahri; Desri Jumiarti; Musawer Hakimi (Jurnal Inovasi Teknologi Pendidikan, 2026)
The high number of learning tools that are not validated is an important highlight of this research problem. This problem arises due to the ineffectiveness of the validation process, which is carried out manually and cannot be carried out in a flexible, time- and material-friendly manner. This research aims to develop a validation system (SVeR) for learning tools based on an open journal system that is valid, practical and effective for measuring the suitability of learning tools created by lecturers. The waterfall development model is the choice for developing this validation system. This research involved 2 expert validators and 16 lecturers who were the subjects of testing the practicality and effectiveness of the system being developed. Data were analyzed using Aiken's V formula for validity testing, percentage techniques with categorization norms for practicality data, and the kappa moment test for effectiveness data. The validity test results based on expert assessment show that SVeR has a very high level of validity with a final content validity coefficient of 0.804. Furthermore, the practicality test results show that SVeR has a practicality level of 94.31% in the convenient category. The same thing applies to the effectiveness test. Based on the test, the kappa moment reached 0.939 with a very high effectiveness category, so it can be concluded that the learning device validation system (SVeR) based on the open journal system for measuring the validity of learning devices has excellent validity, practicality and effectiveness